Vibration Signature of Roller Bearing’s Faults - Ahmed H. Osman; Ahmed A. Salman; Khaled M. Fawzy (European Scientific Journal, ESJ, 2019)
Centrifugal pumps are widely used in many industrial applications. Defective pumps cause higher rate of energy loss with related overall performance degradation. Mechanical components fail due to decrease in pump’s strength or an increase in the force acting on it. Rolling bearings are one of the major components of the centrifugal pumps. Bearings are critical mechanical components in industrial machines. Bearing failure is often attributed to be one of the major causes of breakdown. Early detection of undesired conditions during the operation of the centrifugal pump has become very important in order to avoid consequential damages. Early detection is also vital for increasing availability and reliability. Automated health monitoring can reduce the outage time and repair costs. Using vibration analysis technique to monitor and evaluate the health of the machines has become an important technique in this field. In this research, we studied the vibration signatures of healthy and faulty conditions of the bearings of a pumping system. The pumping system consists of centrifugal pump and electrical motor. The vibration signatures analyze the bearing status with respect to the normal operation. The paper shows how to identify if there is a problem in the outer race of the Bearing Pass Frequency Outer Race (BPFO).